KAZAKHSTAN: PROBLEMS OF DEVELOPING THE OIL AND GAS SECTOR AND IMPROVING THE SYSTEM FOR TAXING SUBSURFACE USERS - KHUSAINOV, Bulat; BERENTAEV, Kanat (CENTRAL ASIA AND THE CAUCASUS, 2004)
In recent decades, the role of the oil and gas industry in the economic development of many states has significantly grown. This also stands true for our republic. The increase in its oil production and export, the country’s main source of revenue, is prompting it to put up an increasingly active fight to conquer energy markets. According to the Ministry of Energy and Mineral Resources, the proven reserves of oil and gas condensate in the republic amount to 4 billion tonnes. In terms of these indices, Kazakhstan is currently one of the leading oil and gas states in the world. But this does not guarantee the country prosperity. It still needs to find its niche on the world markets offering the best operating performance and political dividends. At present, the oil and gas sector accounts for approximately 14% of the gross domestic product (GDP). This is essentially the same as the total contribution of the republic’s transportation and construction sectors to the GDP, whereby in the past five years the share of the oil and gas industry in the GDP grew 2.1-fold (see Table 1). Throughout industry as a whole, it amounts to 10.2%, increasing in these same years by 2.4-fold, and in construction it has risen by more than 1.5-fold, which shows the intensive introduction of new facilities in this sector. Whereas in 2003, total oil production in Eu-rope and Eurasia amounted to 101.3% of the 1985 level (in 2002—97.2%) and in Russia to 78%, in Kazakhstan it increased by 230%. This clearly con-firms that the republic is steering toward intensive development of the oil and gas industry, particularly oil production. Since 1996, the production of oil and gas condensate in the country has been rising steadily (in the first half of the 1990s, particularly in 1994-1995, these indices were perceptibly lower than in 1985-1990). Today, Kazakhstan occupies 18th place among over 60 oil producing states in the world in terms of raw hydrocarbon production, and fourth among the European and Eurasian countries (after Russia, Great Britain, and Norway). And whereas in 1985 its share in the total oil production volume of Europe and Eurasia was equal to 2.8%, in 2003 it was on the order of 6.5% (in Russia, 67.2% and 51.5%, in Norway, 4.9% and 18.7%, and in Great Britain, 15.8% and 12.9%, respectively). In 2003, compared with 2002, the oil production growth rates in Kazakhstan rose to 8.3%. A comparative analysis of the changes in GDP dynamics and oil production in the republic for the past ten years shows that the development rates in this sphere are much faster than similar indices for the economy as a whole. The growth in GDP for this period amounted to 123.4%, and the oil production